The Combination of Fractionated Erbium:YAG Laser Skin Microporation and Topical Imiquimod Is A New, Safe And Efficient Strategy for the Treatment of Actinic Keratosis and Basal Cell Carcinoma: Report of Two Pilot Studies - Haering, N.; Boehler, C.; Barlas, K.; Dertinger, S.; Strohal, R. (Journal of Dermatologic Research And Therapy, 2015)
Two pilot studies evaluate fractional Er:YAG laser microporation to enhance topical imiquimod delivery for actinic keratosis and basal cell carcinoma. The approach seeks to increase epidermal penetration while limiting systemic exposure. Early results suggest acceptable tolerability and lesion response, supporting larger controlled trials.
Keywords: basal cell carcinoma (BCC); actinic keratosis (AK); fractionated erbium:YAG laser; skin micropores; imiquimod; treatment efficacy